PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK PALLET BESI(STUDI KASUS PT SHAKA KREASI MANDIRI) - Vicky Mulya (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
This research aims to determine the partial and simultaneous influence of product quality and price variables on purchasing decisions for iron pallet products at PT. Shaka Kreasi Mandiri. All consumers of PT. Shaka Kreasi Mandiri is the population in this research. Purposive sampling is the sampling technique used in this research. In carrying out the test using SPSS 29 and the analysis process used in this research consists of several stages including validity and reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing with the T test, F test, and coefficient of determination. (R2). The results of the research that has been carried out show that there is a positive and significant relationship between product quality and purchasing decisions. Where the calculated t value is (3.031 > 1.659). Price and purchasing decisions have a positive and significant influence. Where the calculated t value > t table (5.318 > 1.659). The influence of product quality and price on purchasing decisions simultaneously has a calculated f value > f table (28.927 > 3.08). So the R-Square value is 35.5%. Thus, 35.5% of purchasing decisions are driven by product quality and price variables, while the rest are influenced by variables not included in the research